Diversity in the Postcolonial State: The case of the return of looted heirlooms from Germany to Namibia in 2019 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The restitution of the bible and the riding whip of Namibian national hero Hendrik Witbooi, which had been looted during colonial conquest by Germany in 1893, triggered a controversy that points to fundamental contradictions of the postcolonial state. In particular, the official narrative that highlights unity over diverse historical experience is called into question. In early 2019, issues coalesced around the question of ownership to the restituted heirlooms. These relate to the colonial roots of the Namibian state and its homogenising thrust.
Keywords: Memory; restitution; territoriality; Postcolonial State; Namibia